2014
DOI: 10.1074/jbc.m113.515932
|View full text |Cite
|
Sign up to set email alerts
|

The Evidence of HeLa Cell Apoptosis Induced with Tetraethylammonium Using Proteomics and Various Analytical Methods

Abstract: Background: Tetraethylammonium is a broad potassium channel blocker applied in neuron research. Results: Tetraethylammonium has the ability to lead cell apoptotic process; various biological and proteomics methods prove this result. Conclusion: Novel biomarkers candidates are found to reveal mechanism of tetraethylammonium-induced apoptosis. Significance: This provides new details on the new molecular pathway involved in apoptosis and gives a broader context in therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
3
6
0
Order By: Relevance
“…The osmolarity of 30 mM TEA in TCM is ~16% higher than control TCM; however, the toxic effects of 30 mM TEA is not due to high osmolarity as the migration and survival of ENCCs in intact explants of E12.5 gut grown in TCM with 19% higher osmolality due to added sucrose did not differ from explants grown in control TCM (data not shown). Our data are consistent with very recent studies showing that exposure to high concentrations of TEA (>2 mM) kills HeLa cells [ 56 ] and cultured hippocampal neurons [ 57 ]. Lower concentrations of TEA (2 mM, 10 mM) or 4-AP (0.1 mM) had no significant effect on ENCC migration ( Fig 4C ), neuritogenesis ( Fig 4D ) or cell death ( Fig 4F ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The osmolarity of 30 mM TEA in TCM is ~16% higher than control TCM; however, the toxic effects of 30 mM TEA is not due to high osmolarity as the migration and survival of ENCCs in intact explants of E12.5 gut grown in TCM with 19% higher osmolality due to added sucrose did not differ from explants grown in control TCM (data not shown). Our data are consistent with very recent studies showing that exposure to high concentrations of TEA (>2 mM) kills HeLa cells [ 56 ] and cultured hippocampal neurons [ 57 ]. Lower concentrations of TEA (2 mM, 10 mM) or 4-AP (0.1 mM) had no significant effect on ENCC migration ( Fig 4C ), neuritogenesis ( Fig 4D ) or cell death ( Fig 4F ).…”
Section: Resultssupporting
confidence: 93%
“…It is therefore highly likely that the decreased neuritogenesis observed after 9 h exposure to 30 mM TEA or 5 mM 4-AP is due to ENCCs being unhealthy. Other recent studies using HeLa cells and cultured hippocampal neurons have also reported that exposure to high concentrations of TEA for 24 h or more results in cell death [ 56 , 57 ]. Proteomics analyses of HeLa cells exposed to high concentrations of TEA revealed changes in proteins involved in a variety of biological functions including oxidative stress responses, protein synthesis and degradation, metabolism and signal transduction [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe any significant changes in cell viability after 24h or 48 h incubation with apamin or TRAM-34. At the same time, treatment of the cells with 10 mM TEA slightly lowered the viability of K562 cells after 48 h. The more significant effect of 10 mM TEA on cancer cell viability was reported earlier [46]: about 50% of cervical cancer HeLa cells were dead after treatment with 10 mM TEA for 48 h. In our assay, 10 mM TEA almost completely blocked cell proliferation after 24 h and 48 h of incubation, whereas negative effect on cell viability was observed only after 48 h. The inhibition of proliferation by TEA was previously shown on C6, 9L glioma, cervical carcinoma SiHA and endometrial adenocarcinoma HEC1-A cell lines [47]. In glioma cells, treatment of the cells with TEA significantly increased the number of reactive oxygen species (ROS) and alteration of B-cell lymphoma protein 2/B-cell lymphoma protein-associated X (Bcl-2/Bax) balance, which further resulted in cell apoptosis [48].…”
Section: Discussionsupporting
confidence: 73%
“…Additionally, the addition of 2.0 mM glycyrrhizin did not have an additive effect with cisplatin in suppressing NCI-H23 cell growth. Cisplatin can induce apoptosis at 2 μg/ml in several cancer cell lines [24,28], and the IC50 of cisplatin for A549 is approximately 12 μM, i.e., 3.6 μg/ml [29]. Therefore, 2.5 μg/ml and 4 μg/ml of cisplatin were used in this study.…”
Section: Resultsmentioning
confidence: 99%